Perspectives in bioethics, science, and public policy - Beever, Jonathan, 1980-; Morar, Nicolae, 1979- (Purdue studies in public policy., 2013)
"In this book, nine thought-leaders engage with some of the hottest moral issues in science and ethics. Based on talks originally given at the annual "Purdue Lectures in Ethics, Policy, and Science," the chapters explore interconnections between the three areas in an engaging and accessible way. Addressing a mixed public audience, the authors go beyond dry theory to explore some of the difficult moral questions that face scientists and policy-makers every day. The introduction presents a theoretical framework for the book, defining the term "bioethics" as extending well beyond human well-being to wider relations between humans, nonhuman animals, the environment, and biotechnologies. Three sections then explore the complex relationship between moral value, scientific knowledge, and policy making. The first section starts with thoughts on nonhuman animal pain and moves to a discussion of animal understanding. The second section explores climate change and the impact of "green" nanotechnology on environmental concerns. The final section begins with dialog about ethical issues in nanotechnology, moves to an exploration of bio-banks (a technology with broad potential medical and environmental impact), and ends with a survey of the impact of biotechnologies on (synthetic) life itself"--